Dendroblatta iani (Rocha e Silva-Albuquerque, 1964) n. comb. (Ectobiidae, Blattellinae) - Lopes, Sonia Maria; Oliveira, Edivar Heeren De; Silva, Luiz Rafael Silva Da (Zootaxa, 2014)
The species of the family Ectobiidae range from small to large in size, and are found in tropical forests, hidden in leaf litter. This is the largest family among the cockroaches, with about 1,740 described species (Bell et al., 2007). In the Ectobiidae, the subfamilies Pseudophyllodromiinae and Blattellinae are differentiated by the position of the hook-shaped phallomere on the right or the left side, respectively, in dorsal view. The genus Xestoblatta Hebard, 1916 was included in the subfamily Blattellinae by Rocha e Silva-Albuquerque (1964), based on a specimen from the State of Pará described as Xestoblatta iani. The structures of the genitalia, the morphological characters and the habitus of the specimen, as illustrated, support the transfer of this species from the genus Xestoblatta to Dendroblatta.